Cryptococcus species (Tremellales) from glacial biomes in the southern (Patagonia) and northern (Svalbard) hemispheres - de Garcia, Virginia (2012)
Cryptococcus species (Basidiomycota) were isolated as the predominant yeast from glacial biomes of both Patagonia (Argentina) and the Svalbard archipelago (Norway). For a selected group of Cryptococcus belonging to Tremellales, assimilative profile, production of extracellular hydrolytic enzymes and ribosomal DNA internal transcribed spacer and large subunit (D1/D2) sequences were analysed. Cryptococcus victoriae, which was originally described from Antarctica, was the most frequently found species at both locations. High variability within the species was observed and described at the genotypic and phenotypic levels, two newly described species were found in both Patagonia and Svalbard: Cryptococcus fonsecae and Cryptococcus psychrotolerans. Two other new species were found only in Patagonia: Cryptococcus frias and Cryptococcus tronadorensis. Three additional new taxa were found, but they are not named as they were only represented by single isolates. © 2012 Federation of European Microbiological Societies. Published by Blackwell Publishing Ltd.